Investigating The Link Between Conflict Management, Compensation, Work Motivation On Employee Performance Sales People - Christian Wiradendi Wolor; Yetti Supriyati; Dedi Purwana (Journal of International Conference Proceedings (JICP), 2019)
In today's modern industry, where intense competition between companies in the global economic era requires companies to always be the foremost and best in providing satisfying services to consumers. In this case the sales force is one of the company's human resources that has a role in achieving the company's goals. This study aimed to investigate the effect of conflict management, compensation, work motivation on the employee performance of sales people. The sampling technique the researchers used is proportional random sampling. In this study, researchers used 200 samples taken. The number of population is one dealer with four different ones, so the sample is also different. The number of sales people who were sampled 200 respondents from 302 salespeople. The sample size is proportional to the population at each dealer. Statistical tools used in this research is Structural Equation Model (SEM). Data are analyzed by using statistical software LISREL 8.5. This study resulted in the finding that Conflict management has positive effect on work motivation. Conflict management has positive effect on employee performance. Compensation has positive effect on work motivation. Compensation has positive effect on employee performance. Work motivation has positive effect on employee performance. Conflict Management also has an indirect influence through work motivation. Compensation also has an indirect influence through work motivation.